2002
DOI: 10.1183/09031936.02.00238102
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chemotherapy-induced pulmonary fibrosis is associated with polymorphic tumour necrosis factor-a2 gene

Abstract: In some patients, chemotherapy (CHT) of cancer can result in pulmonary inflammation and fibrosis, eventually leading to respiratory insufficiency.As animal studies have underlined the importance of major histocompatibility complex (MHC) genes in the susceptibility to bleomycin (BLM)-induced pulmonary fibrosis, the authors typed human leukocyte antigen-DR (HLA-DR) and tumor necrosis factor (TNF) genes in patients treated for Hodgkin's disease by a therapy including bleomycin.Patients were divided into pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
0
10
1
Order By: Relevance
“…The risk of chemotherapy-induced pulmonary fibrosis has been associated with a polymorphism into the TNF␣2 gene and increased TNF production. 30 Also in mice, the relative resistance of the BALB/c strain to develop fibrosis after bleomycin instillation has been associated with impaired TNF production and its p75 receptor up-regulation 28,29 rather than to a reduced modulation of TGF-␤RI and TGF-␤RII 42,43 Soluble, rather than transmembrane, TNF is required for developing fibrotic lesions via lymphocyte recruitment and their production of TGF-␤1. Kapancy and colleagues were the first to localize TNF stored in type II alveolar pneumocytes and to postulate the need for epithelialmesenchymal cross-talk involving TNF and TGF-␤1 toward fibrosis development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of chemotherapy-induced pulmonary fibrosis has been associated with a polymorphism into the TNF␣2 gene and increased TNF production. 30 Also in mice, the relative resistance of the BALB/c strain to develop fibrosis after bleomycin instillation has been associated with impaired TNF production and its p75 receptor up-regulation 28,29 rather than to a reduced modulation of TGF-␤RI and TGF-␤RII 42,43 Soluble, rather than transmembrane, TNF is required for developing fibrotic lesions via lymphocyte recruitment and their production of TGF-␤1. Kapancy and colleagues were the first to localize TNF stored in type II alveolar pneumocytes and to postulate the need for epithelialmesenchymal cross-talk involving TNF and TGF-␤1 toward fibrosis development.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in bleomycin susceptibility between responder and nonresponder mouse strains has been correlated with their different production of TNF. [27][28][29][30] We investigated whether an increase in TNF production was associated with the exacerbated bleomycin-induced fibrosis in KOϾWT chimeras. Indeed, TNF production was significantly higher in KOϾWT than in WTϾWT chimeras (Figure 5A), and IF analysis indicated that both SP-C ϩ type II pneumocytes and CD11b ϩ leukocytes were responsible for TNF production ( Figure 5B).…”
Section: Bone Marrow-derived Sparc Regulates Tnf Productionmentioning
confidence: 99%
“…Polymorphisms of the microsatellites TNFa and TNFd were analyzed using optimized PCR conditions and fluorescent labeled primers as described (27,28). Similarly IL-10-1064 was analyzed as described (29) using the modified primers 5=GAAGTCCTGATGTCACTGCCC and 5=-TET-CT-ATCCCTACTTCCCCTTCCC.…”
Section: Analysis Of Cytokine Gene Polymorphismsmentioning
confidence: 99%
“…13,14 Some authors reported the presence of severe and diffuse interstitial fibrotic involvement in the neoadjuvant therapy group. 6,7 However, there is a lack of sufficient and quantitative data regarding the effect of neoadjuvant therapy on pulmonary vessels and bronchi. Thus, the hypothesis of this study was that the pulmonary structures of patients who received neoadjuvant chemotherapy may have been damaged and that this damage could lead to surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Thus, we investigated histopathological changes possibly caused by neoadjuvant chemotherapy and their effect on the tensile forces of pulmonary structures. Tensile stress is caused by an applied load that tends to elongate the material along the axis of the applied load; i. e., the stress is caused by pulling the material.…”
Section: Introductionmentioning
confidence: 99%